Sosialisasi Hak Konstitusional Warga yang Terkena Dampak Bencana di Aceh Tamiang - Ismed Batubara; Arif Hadian; Yeltriana Yeltriana; Dalfatara Dalfatara; Nazwa Fitri (Indo Publishing, 2026)
This community service program takes the form of counseling on post-flood recovery and strengthening of children's education in Kuala Simpang, specifically through the